Uji Aktivitas Tabir Surya Ekstrak Etanol Daging Buah Jambu Biji Merah dan Jambu Biji Putih (Psidium guajava L.) - Mustika Furi; Armon Fernando; Musyirna Rahmah Nasution (Jurnal Penelitian Farmasi Indonesia)
Guava fruit (Psidium guajava. L.) is consist at phenolics content that have antioxidant activirt and the possibility of using as sunscreen. The purpose of this research was to determine the concentration of extracts that have a potential sunscreen profile by determining the value of erythema transmission, pigmentation transmission and sun protection factor (SPF). Sunscreen activity was carried out in vitro using UV-Vis Spectrophotometer. Ethanol extract, red guava and white guava fruit are made to concentration of 100; 150; 200; 250 ppm, each absorption was measured in the UV A and UV B areas. As result the extract of red guava at a concentration of 250 ppm had %Te value was 15.32% which was included in the category fast tanning, %Tp was 25.4% which was included in the sunblock category and the SPF value was 8,228 which was categorized as maximum protection. The extract of white guava at a concentration of 250 ppm had %Te value of 12.51% which was included in Suntan standard category, the % Tp value was 21.97% which belongs to the sunblock category and the SPF value was 8, 945 which was categorized as maximum protection. Keyword : Guava fruit, SPF, %Te, %Tp